Adult orbital xanthogranuloma - a case report - E, Rashidov; M, Babakalanova; M, Molitor; Z, Špůrková (Acta chirurgiae plasticae, 2023)
The periorbital plastic surgery, especially upper and lower blepharoplasty is a very common surgical procedure. Usually the preoperative finding is typical, the surgery routine without unexpected surprises and postoperative course is smooth, quick and without complications. However, periorbital area can also be the source of unexpected findings and peroperative surprises. In this article we present a rare case of a specific disorder - adult onset orbital xantogranuloma in a 37-year-old woman who was treated for recurrences of facial adult orbital xantogranuloma by surgical excisions at the Department of Plastic Surgery, University Hospital Bulovka.
Keywords: ženské pohlaví; Female; Plastic Surgery Procedures; Hospitals, University; blefaroplastika; hematologické nádory; Humans; lidé; dospělí; obličej; nádory kůže; Skin Neoplasms; Hematologic Neoplasms; nemocnice univerzitní; Adult; Face; zákroky plastické chirurgie; Blepharoplasty